Competency‐based education: Multiple approaches‐a single institution. Issue 3 (26th June 2019) - Hagan‐Short, Michelle; Addison, Paul
Abstract: The purpose of this paper was to describe the development of two competency‐based curricula for existing programs at the largest community college with single accreditation serving nearly 160, 000 students each year. Utilizing a competency framework and industry partners, program level and students level outcomes were defined to adequately prepare students to meet industry needs. Although the programs were developed and assessed differently, each captured the spirit of competency‐based education, which is to provide a flexible learning environment focusing on mastery of academic content through assessments, regardless of time, pace, or place of learning. This paper identifies how a single institution that already provides a variety of alternative delivery modes to meet student needs can successfully develop competency‐based initiatives in two very different ways. The development effort was realized through exemplary partnerships with local businesses, industries, and other educational institutions. Although the development of the content was completed and piloted, events related to the learning management platform's availability along with difficulties in administering the program, due to exceptions in procedure, resulted in an indefinite suspension of the program. The paper further discusses the need for capital, administrative support, and an understanding of processes and approvals of accrediting organizations and the Department of Education.